Construction of sodium alginate/konjac glucomannan/chitosan oligosaccharide/Zeolite P hydrogel microspheres loaded with potassium diformate for sustained intestinal bacterial inhibition. (5th June 2022) - Yang, ZhongXin; Yang, YuHang; Zhang, XiaoNan; Fu, Bei; Xu, WenQin; Xue, DengPing; Chen, NanChun; Wang, XiuLi; Xie, QingLin
Graphical abstract: Highlights: Optimization of preparation of hydrogel microspheres by using response surface methodology. ALG/KGM/COS/Zeolite P hydrogel microspheres with pH sensitivity. Zeolite P as a key factor to control release of hydrogel microspheres. The great potential of ALG/KGM/COS/Zeolite P hydrogel microspheres in intestinal bacterial inhibition. Abstract: Owing to their non-toxicity and non-resistance to bacteria, potassium diformate (KDF) bacterial inhibitors may act as antibacterials in the intestinal tract and are good alternatives to antibiotics; however, KDF has low intestinal utilization rate when used directly. We prepared pH-sensitive sodium alginate (ALG)/konjac glucomannan (KGM)/chitosan oligosaccharide (COS)/Zeolite P hydrogel microspheres for the slow release of KDF using a complex coalescence method to ensure better bacterial inhibition and balance of the gut flora in the intestine. We found that the hydrogen bonding interaction between ALG and KGM, chelating interaction between ALG and Ca 2+, and electrostatic interaction of COS together build a three-dimensional porous network structure. Notably, Zeolite P contributes to the formation of a dense three-dimensional network structure to avoid premature release of KDF in the stomach, improve the stability of KDF and prolong its release in the intestine. In vitro bacterial inhibition experiments showed that the maximum antibacterial rates of the hydrogel microspheres were 92 ± 3%, 86 ± 4%, and 88 ± 4% against Escherichia coli, Staphylococcus aureus, and Bacillus subtilis, respectively, indicating that they can effectively inhibit bacterial growth and balance the bacterial flora. In addition, hydrogel antibacterial microspheres are biodegradable and non-cytotoxic. Thus, ALG/KGM/COS/Zeolite P hydrogel microspheres may be used for colon-targeted delivery of drugs.